2017
DOI: 10.1002/2016je005240
|View full text |Cite
|
Sign up to set email alerts
|

Titan's atmosphere and climate

Abstract: Titan is the only moon with a substantial atmosphere, the only other thick N2 atmosphere besides Earth's, the site of extraordinarily complex atmospheric chemistry that far surpasses any other solar system atmosphere, and the only other solar system body with stable liquid currently on its surface. The connection between Titan's surface and atmosphere is also unique in our solar system; atmospheric chemistry produces materials that are deposited on the surface and subsequently altered by surface‐atmosphere int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
203
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(212 citation statements)
references
References 600 publications
(1,223 reference statements)
3
203
0
Order By: Relevance
“…On Titan, observational studies show that the maximum surface temperature stays close to the equator during Titan's year (Jennings et al, 2016); yet cloud observations show a significant seasonal variation (e.g., Turtle et al, 2018). Models of Titan's climate vary depending on their physical aspects (Hörst, 2017), with some models associating polar clouds with the Hadley cell ascending branch (e.g., Schneider et al, 2012) while others locate the ascending branch at midlatitudes (e.g., Lora et al, 2015). The warmest latitude also varies between models (e.g., the difference between dry and moist cases in Newman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On Titan, observational studies show that the maximum surface temperature stays close to the equator during Titan's year (Jennings et al, 2016); yet cloud observations show a significant seasonal variation (e.g., Turtle et al, 2018). Models of Titan's climate vary depending on their physical aspects (Hörst, 2017), with some models associating polar clouds with the Hadley cell ascending branch (e.g., Schneider et al, 2012) while others locate the ascending branch at midlatitudes (e.g., Lora et al, 2015). The warmest latitude also varies between models (e.g., the difference between dry and moist cases in Newman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that overall haze production rates might be similar for a range of stellar spectra, implying that very Titan-like exoplanets could exist around a wide range of host stars. However, it should be noted that we rely on a parameterization of haze production using haze precursors to arrive at our estimated production rates, and that the actual chemical pathways leading to haze formation are as yet poorly understood (see Hörst 2017, for a review). For example, both models (e.g., Lavvas et al 2013) and observations (Coates et al 2007;Crary et al 2009;Liang et al 2007;Wahlund et al 2009;Waite et al 2007) of Titan's atmosphere indicate that ion chemistry plays an important role in haze formation; our photochemical model lacks ion chemistry, and therefore our haze formation picture is incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, aerosols that form at low pressures through the actions of photochemistry-hazes-have an advantage since there is no need for lofting. For example, optical transits of Saturn's moon Titan probe altitudes upwards of 300 km (10-100 µbar) above the surface due to opacity from photochemical hazes (Robinson et al 2014), while haze formation occurs at pressures as low as 0.1 nbar at an altitude of 1000 km, which is comparable to the solid body radius of Titan of 2575 km (Hörst 2017). Morley et al (2013Morley et al ( , 2015 showed that a flat spectrum for GJ 1214b can be generated using photochemical hazes if ≥10% of the products of methane and nitrogen photolysis are converted into hazes with particle radius ∼0.1 µm.…”
Section: Introductionmentioning
confidence: 99%